Perancangan Rusunawa Tambora di Jakarta Barat dengan Penerapan Arsitektur Bioklimatik - Nurcholis, Ade (Fakultas Teknik - Universitas Bung Karno, 2024)
Tambora Flats is one of the vertical housing in West Jakarta that has functioned as a residence for the lower middle class community built in 2013. The survey results show that a redesign is needed to improve the quality of housing according to vertical residential space standards and efficiency through design that takes into account climate and the environment. This working paper is the result of the redesign process of tambora flats with a bioclimatic approach. The method used in this discussion is to conduct research on environmental needs and contexts, bioclimatic analysis from the site, space program and form approach. The results of the discussion are that the bioclimatic approach provides direction for the design of the placement of building mass blocks, facades, and processing of the site surface according to contextual needs.